2018
DOI: 10.1080/00498254.2018.1451667
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the absorption, distribution, metabolism, excretion and mass balance of doravirine, a non-nucleoside reverse transcriptase inhibitor in humans

Abstract: Absorption, distribution, metabolism and elimination of doravirine (MK-1439), a novel non-nucleoside reverse transcriptase inhibitor, were investigated. Two clinical trials were conducted in healthy subjects: an oral single dose [C]doravirine (350 mg, ∼200 µCi) trial (n = 6) and an intravenous (IV) single-dose doravirine (100 µg) trial (n = 12). In vitro metabolism, protein binding, apparent permeability and P-glycoprotein (P-gp) transport studies were conducted to complement the clinical trials. Following ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(103 citation statements)
references
References 15 publications
7
96
0
Order By: Relevance
“…8 In the current trial, a lack of clinically meaningful effects on doravirine PK was anticipated based on doravirine's pH-independent aqueous solubility and high permeability. 19 In addition, the chemical structure of doravirine 20 does not contain the chelating motifs that render HIV integrase strand transferase inhibitors susceptible to divalent cation binding by cations present in antacid salts, with a subsequent loss of bioavailability. 21,22 Along with the data from the current trial, these properties support that doravirine is unlikely to interact with acid-reducing agents or cationcontaining antacids.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the current trial, a lack of clinically meaningful effects on doravirine PK was anticipated based on doravirine's pH-independent aqueous solubility and high permeability. 19 In addition, the chemical structure of doravirine 20 does not contain the chelating motifs that render HIV integrase strand transferase inhibitors susceptible to divalent cation binding by cations present in antacid salts, with a subsequent loss of bioavailability. 21,22 Along with the data from the current trial, these properties support that doravirine is unlikely to interact with acid-reducing agents or cationcontaining antacids.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] In the United States, doravirine is indicated for administration once daily at a dose of 100 mg, in combination with other antiretroviral agents, for the treatment of HIV-1 infection. 25 In vitro studies and clinical drug interaction studies indicated that CYP3A-mediated metabolism is a major contributor to the elimination of doravirine. 22,23 The rapid absorption of doravirine has been shown to result in a median time to maximum concentration (t max ) of 1 to 4 hours and a half-life of 12 to 19 hours for single oral doses of 6 to 1200 mg, 23 and a geometric mean maximum plasma concentration (C max ) of 2.26 μM was achieved at steady state following once-daily dosing.…”
mentioning
confidence: 99%
“…25 In vitro studies and clinical drug interaction studies indicated that CYP3A-mediated metabolism is a major contributor to the elimination of doravirine. 25 Based on metabolism and elimination pathways, methadone and doravirine are not expected to demonstrate any meaningful DDIs upon coadministration. The oxidative metabolite M9 was the major metabolite of doravirine observed both in vitro in preparations from human liver and in vivo in human excreta and plasma.…”
mentioning
confidence: 99%
See 2 more Smart Citations